Characteristics and controlling factors of Lucaogou formation shale reservoir in the northern edge of Bogda Mountain, the Junggar Basin, China - Fanjian Jia; Ruichao Guo; Jianwei Wang; Leqiang Zhao; Zhiping Wu (Journal of Petroleum Exploration and Production Technology)
Abstract The practice of oil and gas exploration has confirmed the existence of recoverable shale oil resources in the Permian Lucaogou Formation on the northern edge of the Bogda Mountains. However, previous research on the development characteristics and main controlling factors of shale oil resources in this area is relatively limited. In order to elucidate the development characteristics and principal controlling factors of the shale deposit in the Lucaogou Formation, the characteristics, physical properties, diagenesis, and influencing factors of the shale ore were investigated utilising data derived from outcrop, drilling, seismic, and geochemical analysis. The findings indicate that the shale of the Lucaogou Formation is prevalent and extensive. The deposit’s lithology is predominantly composed of dark grey and grey-black mud shale, interspersed with thin layers of dark grey and grey-black sandy mud shale and dolomite mud shale. The most prevalent minerals are carbonate minerals, followed by feldspar and quartz, with a notable proportion of brittle minerals. The deposit is primarily composed of dissolution pores, bedding fractures, and structural fractures, with a porosity of 1.23–3.26% and permeability of 0.012–0.076 mD, which are characteristic of ultra-low porosity and ultra-low permeability deposits. Among the three deposit types, the sandstone type exhibits the most favourable physical properties, followed by the dolomite type and the shale type, which displays the least favourable properties. The shale of the Lucaogou Formation is currently in the middle diagenetic phase, which is characterised by compaction, cementation (carbonate cementation, mudstone cementation, pebble cementation), and dissolution. The destructive effect of compaction and cementation on the physical properties is counterbalanced by the constructive effect of dissolution. The diagenetic environment has gradually changed from an alkaline environment to a slightly alkaline, slightly acidic stage.